Is it essential for the combination of GOLD C and D groups in COPD patients - Tao Li; Ping Zhang; Qing Song; Cong Liu; Ling Lin; Yuqin Zeng; Ping Chen (Medicine, 2026)
The global initiative for chronic obstructive lung disease (GOLD) 2023 combined the C and D groups into the E group. This study aimed to explore the necessity of combining the GOLD C and D groups based on prognosis and inhaled treatment response in patients with chronic obstructive pulmonary disease (COPD). This study retrospectively analyzed data from the Real-world Diapnosis and Treatment of COPD cohort study from January 2017 to June 2022. The baseline demographic and clinical data were organized. According to the GOLD 2017, patients were classified into 4 groups (A, B, C, and D). At follow-up, the number of moderate-to-severe exacerbations in 1 year and all-cause mortality in 3 years were recorded. A total of 4970 COPD patients were included in this study, with a mean age of 62.4 ± 8.4 years; 86.9% were male, and 77.6% were smokers. The GOLD C group included 156 (3.1%) patients. Logistic regression with stratified adjustment showed that patients in the GOLD A and B groups had the lowest risk of future exacerbation (A group: odds ratio [OR] = 0.369, 95% confidence interval [CI] = 0.249–0.546; B group: OR = 0.447, 95% CI = 0.339–0.671), frequent exacerbation (A group: OR = 0.291, 95% CI = 0.169–0.503; B group: OR = 0.458, 95% CI = 0.296–0.709), and hospitalization (A group: OR = 0.349, 95% CI = 0.219–0.556; B group: OR = 0.394, 95% CI = 0.267–0.582), whereas patients in the GOLD D group had similar risk values to patients in the GOLD C group. Stratified logistic regression also showed that different inhaled treatments had no impact on the risk of future exacerbation, frequent exacerbation, and hospitalization in the GOLD C group, while in GOLD D group, long-acting β-2-agonist/long-acting muscarinic antagonist (LABA/LAMA) or LABA/LAMA/inhaled corticosteroids could decrease the risk of future any exacerbation and frequent exacerbation but the risk of hospitalization was similar among different inhaled treatment groups. The GOLD C group, as the smallest group, showed a similar prognosis to the GOLD D group. The effect of different inhaled treatments was almost the same in the GOLD C group, while LABA/LAMA and LABA/LAMA/inhaled corticosteroids were superior for patients in the GOLD D group.